2023
DOI: 10.1111/cpr.13442
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular mitochondrial transfer alleviates pyroptosis in dental pulp damage

Abstract: Mitochondrial transfer is emerging as a promising therapeutic strategy for tissue repair, but whether it protects against pulpitis remains unclear. Here, we show that hyperactivated nucleotide‐binding domain and leucine‐rich repeat protein3 (NLRP3) inflammasomes with pyroptotic cell death was present in pulpitis tissues, especially in the odontoblast layer, and mitochondrial oxidative stress (OS) was involved in driving this NLRP3 inflammasome‐induced pathology. Using bone marrow mesenchymal stem cells (BMSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…They confirmed that odontoblasts could receive exogenous mitochondria through tunneling nanotubes, thereby reducing mitochondrial dysfunction and ROS-NLRP3 inflammasome-triggered cell pyroptosis. When stress conditions occur, pyroptotic odontoblasts would increase TNF-αto-promoted tunneling nanotubes formation via NF-κB signaling, resulting in elevated mitochondrial transfer efficiency, which can be recognized as a self-defense mechanism [106]. To sum up, stabilizing mtDNA and developing effective measures to remove cytosolic mtDNA in time and transferring healthy mitochondria may be important for controlling inflammatory response and preventing irreversible pulp damage.…”
Section: Pulpitismentioning
confidence: 99%
“…They confirmed that odontoblasts could receive exogenous mitochondria through tunneling nanotubes, thereby reducing mitochondrial dysfunction and ROS-NLRP3 inflammasome-triggered cell pyroptosis. When stress conditions occur, pyroptotic odontoblasts would increase TNF-αto-promoted tunneling nanotubes formation via NF-κB signaling, resulting in elevated mitochondrial transfer efficiency, which can be recognized as a self-defense mechanism [106]. To sum up, stabilizing mtDNA and developing effective measures to remove cytosolic mtDNA in time and transferring healthy mitochondria may be important for controlling inflammatory response and preventing irreversible pulp damage.…”
Section: Pulpitismentioning
confidence: 99%